Leaf Impressions of Terminalia (Combretaceae) and Daphnogene (Lauraceae) from the Middle Siwalik of the Chatara-Barahakshetra Area, Eastern Nepal - Adhikari, Purushottam; Srivastava, Gaurav; Mehrotra, Rakesh C.; Adhikari, Drona; Shrestha, Keshav; Uhl, Dieter; Paudayal, Khum N. (Bulletin of the Department of Geology, 2018)
Leaves of Terminalia (Combretaceae) and Daphnogene (Lauraceae) are described from the lower member of Lower Siwalik of Chatara- Barahakshetra area, eastern Nepal. The habit, habitat and present day distribution of the comparable extant taxa indicates the existence of tropical to sub-tropical evergreen to semi evergreen forest with humid climate in the area during the deposition of the Siwalik sediments. Bulletin of Department of Geology, vol. 20-21, 2018, pp: 21-28